2012
DOI: 10.1016/s0140-6736(11)61650-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the incidence of pneumonia of vitamin D supplementation by quarterly bolus dose to infants in Kabul: a randomised controlled superiority trial

Abstract: SummaryBackgroundVitamin D has a role in regulating immune function, and its deficiency is a suggested risk factor for childhood pneumonia. Our aim was to assess whether oral supplementation of vitamin D3 (cholecalciferol) will reduce the incidence and severity of pneumonia in a high-risk infant population.MethodsWe did a randomised placebo-controlled trial to compare oral 100 000 IU (2·5 mg) vitamin D3 with placebo given to children aged 1–11 months in Kabul, Afghanistan. Randomisation was by use of a compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
197
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(210 citation statements)
references
References 29 publications
4
197
0
8
Order By: Relevance
“…Similar to our study another Indian study by Choudhary and Gupta, used vitamin D for 5 days and compared with placebo in cases with pneumonia showed there is no effect in the time of recovery from the disease [19]. Another study from Afghanistan on the role of supplementing vitamin D in the incidence of childhood pneumonia and its severity, showed no additional beneficial effect of vitamin D when given to children with pneumonia [9].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Similar to our study another Indian study by Choudhary and Gupta, used vitamin D for 5 days and compared with placebo in cases with pneumonia showed there is no effect in the time of recovery from the disease [19]. Another study from Afghanistan on the role of supplementing vitamin D in the incidence of childhood pneumonia and its severity, showed no additional beneficial effect of vitamin D when given to children with pneumonia [9].…”
Section: Discussionsupporting
confidence: 85%
“…Other sources are egg yolk, fatty fish such as tuna, sardines or сod liver oil [8]. The binding of vitamin D to its receptors results in increased intracellular formation of antimicrobial compounds, such as cathelicidins which serve a critical role in innate immunity against invasive bacterial infection [9]. Charan et al reported that vitamin D induces monocyte differentiation and inhibits lymphocyte proliferation thus increasing the immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RCT of highest quality and greatest application to western populations, Murdoch 2012, 36 found that vitamin D supplementation over two winters did not reduce cold or flu illness in 322 New Zealand university and/or health care workers. The majority of other trials, including a large trial of infants in Kabul Afghanistan, 37 did not find a reduction in respiratory infections. One trial of Mongolian children with profound vitamin D deficiency (17.5 nmol/L) found a reduction of 0.35 respiratory tract infections over 3 months.…”
Section: Belief 3: Vitamin D Reduces Respiratory Tract Infections Obsmentioning
confidence: 96%